Vitamin D3 enhances the effects of omega‐3 oils against metabolic dysfunction‐associated fatty liver disease in rat. (12th November 2021) - Refaat, Bassem; Abdelghany, Abdelghany H.; Ahmad, Jawwad; Abdalla, Osama M.; Elshopakey, Gehad E.; Idris, Shakir; El‐Boshy, Mohamed
Abstract: This study investigated the effects of omega‐3 oils (OM) and/or vitamin D3 (VD) against metabolic dysfunction‐associated fatty liver disease (MAFLD). Forty rats were divided into negative (NC) and positive (PC) controls, OM, VD, and OM + VD groups, and MAFLD was induced by high‐fat/high‐fructose diet (12 weeks). Oral OM (415 mg/kg/day) and/or intramuscular VD (290 IU/kg/day) were given for 4 weeks (5 times/week). The PC animals were markedly obese and had hyperglycemia, insulin resistance, dyslipidemia, elevated liver enzymes, abnormal hepatic histology, and increased caspase‐3 with apoptosis than the NC group. The expression of hepatic peroxisome proliferator‐activated receptor‐α (PPAR‐α; 5.3‐fold), insulin induced gene‐1 (INSIG1; 7.8‐fold), adiponectin receptor‐1 (AdipoR1; 4.4‐fold), and leptin receptor (LEPR; 6‐fold) declined, while PPAR‐γ (3.7‐fold) and sterol regulatory element‐binding protein‐1 (SREBP1; 2.4‐fold) increased, in the PC than the NC group. Leptin (2.2‐fold), malondialdehyde (2.1‐fold), protein carbonyl groups (17.3‐fold), IL‐1β (4.4‐fold), IL‐6 (2.1‐fold), TNF‐α (1.8‐fold) also increased, whereas adiponectin (2.8‐fold) glutathione (2.1‐fold), glutathione peroxidase‐1 (2.4‐fold), glutathione reductase (2.2‐fold), catalase (1.4‐fold), and IL‐10 (2.8‐fold) decreased, in the PC livers. Both monotherapies attenuated obesity, metabolic profiles, and PPAR‐γ/SREBP1/leptin/Caspase‐3/apoptosis, while induced PPAR‐α/adiponectin/AdipoR1/LEPR/INSIG1. The monotherapies also reduced the oxidative stress and pro‐inflammatory markers and increased the antioxidant and anti‐inflammatory molecules. However, the OM effects were better than VD monotherapy. Alternatively, the co‐therapy group showed the greatest ameliorations in liver functions, lipid‐regulatory molecules, oxidative stress, inflammation, and apoptosis. In conclusion, while OM monotherapy was superior to VD, the co‐therapy protocol displayed the best alleviations against MAFLD, possibly by enhanced modulation of metabolic, antioxidant, and anti‐inflammatory pathways.